Characteristic of bioplastic’s physical and mechanical (Study on Tapioca Concentration and Composition Mixture of Plasticizer) - Harsojuwono, Bambang Admadi; Arnata, I Wayan (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 3 No 1 (2016), 2016)
This study aims to (1) the effect of the concentration of starch and  ratio mixture of plasticizer to the physical and mechanical characteristics of bioplastics (2) determine the concentration of starch and plasticizer RATIO mixture  that results in physical and mechanical characteristics of bio plastics best. The experiment was conducted using a factorial randomized block design. The first factor is the concentration of tapioca consisting of 3 levels 4%, 5% and 6% (w / w). The second factor is the   mixture plasticizer ratio  of glycerol and sorbitol   consisting of 5 levels ie (100: 0)%, (95: 5)%, (90:10)%, (85:15)%, (80:20)% b / b. Each combination of treatments classified into 2 time  processing bio plastics, so there are 30 experimental units. Variables observed water content, elongation at break, tensile strength and Young's modulus . The data obtained were analyzed of variant and  test of Duncan's. The results showed that the concentration of tapioca and  mixture plasticizer had no effect on water content but significant effect on the elongation at break, tensile strength and Young's modulus. The concentration of starch 6% with a ratio of mixture of plasticizers glycerol: sorbitol ( 100: 0) produces the best characteristics of bioplastics with water content of 3.98%, elongation at break of 18.75%, the tensile strength of 930 MPa and a Young's modulus of 50 MPa.
Keywords: Bioplastics; concentration of tapioca; ratio of glycerol and sorbytol